Evaluating Indirect Ecological Effects of Biological Control. Key Papers From the Symposium 'Indirect Ecological Effects in Bio 2000
DOI: 10.1079/9780851994536.0099
|View full text |Cite
|
Sign up to set email alerts
|

Insect biological control and non-target effects: a European perspective.

Abstract: A 4-year research project on 'Evaluating Environmental Risks of Biocontrol Introductions in Europe' (ERBIC) is described, and early results are presented. The project focuses on arthropod biological control (using both microbial and macrobial agents), and uses literature review, case studies with empirical work and various types of modelling to illuminate risk to non-target organisms. These methods will hopefully lead to the development of usable methodologies and guidelines for risk assessment in arthropod bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 16 publications
2
51
0
Order By: Relevance
“…As a generalization, a strong case can be made for the view that biological control contributes to a reduction in pesticide use with corresponding benefits to the environment. While it should not be assumed that introduced biological control agents pose no risk to native species and ecosystems, history suggests that there have been remarkably few problems, even through the many decades when regulation was virtually non-existent (Lynch et al 2001;van Lenteren et al 2006a). The recently published regulatory guidelines are intended to produce a careful analysis of the establishment potential of an imported species in a new environment and any adverse effects on non-target organisms and ecosystem functions that may then arise.…”
Section: Risks Benefits and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a generalization, a strong case can be made for the view that biological control contributes to a reduction in pesticide use with corresponding benefits to the environment. While it should not be assumed that introduced biological control agents pose no risk to native species and ecosystems, history suggests that there have been remarkably few problems, even through the many decades when regulation was virtually non-existent (Lynch et al 2001;van Lenteren et al 2006a). The recently published regulatory guidelines are intended to produce a careful analysis of the establishment potential of an imported species in a new environment and any adverse effects on non-target organisms and ecosystem functions that may then arise.…”
Section: Risks Benefits and Regulationmentioning
confidence: 99%
“…Pre-release screening of entomophagous biological control agents lagged behind their weed counterparts until the warnings by Howarth (1983Howarth ( , 1991 and Lockwood (1993), which raised concerns about possible impacts on non-target species. Interestingly, an analysis of published and unpublished information found that only 1.5% of entomophagous biological control agents introduced before 1999 had undergone any pre-release host specificity testing (Lynch et al 2001). Yet, despite the fact that non-target effects of entomophagous biological control agents were rarely considered prior to import and release, there are only a few known cases where any adverse effects can be attributed to the release of such organisms (van Lenteren et al 2006a).…”
Section: Risks Benefits and Regulationmentioning
confidence: 99%
“…Many exotic natural enemies released in European greenhouses are unlikely to survive winter, but some may. For instance, a research program funded by the European Union established the lack of overwintering capability in the nearctic generalist predator Orius insidiosus (Say) in Italy, but indicated that the Asian lady beetle H. axyridis may successfully overwinter in that area (Lynch et al 2001). Certainly, overwintering ability of an introduced species may depend upon the geographic origin of the strain used.…”
Section: Assessing Environmental Risks Of Exotic Generalist Predatorsmentioning
confidence: 99%
“…Some even fear that introductions of nonindigenous natural enemies for biological control may have already caused extinctions of target and nontarget organisms. However, there is some dispute as to the validity of the evidence brought forward to prove the harmful side-effects of biocontrol introductions (see and Howarth 2001 for conflicting views; see also Lynch et al 2001 for an overview of the evidence). In short, despite the massive numbers of non-native natural enemies that have been released in classical and augmentative biological control programs, there is no unequivocal evidence that introduced arthropods have been the direct cause of species extinctions.…”
Section: Drawbacks Of (Exotic) Generalist Predatorsmentioning
confidence: 99%
“…Non-target effects have become important in insect biological control projects over the past decade, and several review papers have addressed this issue (Howarth, 1991;Simberloff & Stiling, 1996;Stiling & Simberloff, 2000;Lynch et al, 2001). Non-target effects may arise if either non-target herbivores or natural enemies present in the habitat are attacked by the biological control agent.…”
Section: Introductionmentioning
confidence: 99%